Eksistensi Batagor sebagai Warisan Kuliner Sunda di Tengah Modernisasi Kota Bandung - Pratama, Carissa Alodia; Chan, Michelle; Sam, Debora Yesua Hadhasa; Chandra, Maximilianus Nathan (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2025)
Bandung is renowned as one of Indonesia's most popular culinary destinations, offering a diverse selection of eateries and unique, mouth-watering dishes. Dishes such as batagor, siomay, surabi, seblak, and peeyeum have become culinary icons, reflecting the rich culture and creativity of its people. The purpose of this study was to examine the diversity of Bandung's culinary traditions and their impact on tourism and the local economy. The research method used was descriptive qualitative. The results show that batagor remains a pioneering traditional Bandung food, popular among all groups